Whole‐Body Multicontact Haptic Human–Humanoid Interaction Based on Leader–Follower Switching: A Robot Dance of the "Box Step". (30th May 2021) - Kobayashi, Taisuke; Dean-Leon, Emmanuel; Guadarrama-Olvera, Julio Rogelio; Bergner, Florian; Cheng, Gordon
Abstract : For physical human–robot interaction (pHRI) where multi‐contacts play a key role, both robustness to achieve robot‐intended motion and adaptability to follow human‐intended motion are fundamental. However, there are tradeoffs during pHRI when their intentions do not match. This paper focuses on bipedal walking control during pHRI, which handles such tradeoff when a human and a humanoid robot having different footsteps locations and durations. To resolve this, a force‐reactive walking controller is proposed by adequately combining ankle and stepping strategies. The ankle strategy maintains the robot's intention based on an analytically‐optimal center of pressure, leading the robot to oppose resistance to multiple contacts from the human. Based on the robot's kinodynamic constraints and/or the confidence of the robot's intention, the stepping strategy updates the robot's footsteps based on the human's intention implied by the multiple contact forces. Consequently, the proposed walking control on pHRI mutually exchanges human–robot intentions in real‐time, thereby achieving coordinated steps. With a full‐sized humanoid robot that is able to detect multi‐contacts in real‐time, we succeeded in performing a long‐term "box‐step" with multi‐contacts pHRI, demonstrating the robustness of our approach. Abstract : The humanoid succeeds in enlarging its step length according to the multicontact force from the partner.